Colloidal dispersions under slit-pore confinement - Zeng, Yan. (Springer theses, recognizing outstanding Ph.D. research, 2012)
This dissertation contributes to the understanding of fundamental issues in the highly interdisciplinary field of colloidal science. Beyond colloid science, the system also serves as a model for studying interactions in biological matter. This work quantitatively investigated the scaling laws of the characteristic lengths of the structuring of colloidal dispersions and tested the generality of these laws, thereby explaining and resolving some long-standing contradictions in the literature. It revealed the effect of confinement on the structuring, independently of specific properties of the confining interfaces. In addition, it resolved the influence of roughness and charge of the confining interfaces on the structuring, as well as providing a method to measure the effect of surface deformability on colloidal structuring. Scientific background -- Experimental section -- Structuring of nanoparticle suspensions confined between two smooth solid surfaces -- Structuring of nanoparticles between modified solid surfaces -- Structuring of nanoparticles confined between a silica microsphere and an air bubble -- Structuring of nonionic surfactant micelles.